Multi-function power electronic interface for hybrid mini-grid systems - Darbyshire, James (Curtin University, 2010)
In the past five years, global interest regarding the development of renewable energy technologies has significantly increased. The conventional electric power generation methods sourced from fossil fuels is now problematic, from both the supply and emission points of view. Fossil fuels are non-renewable limited resources that have taken millions of years to form; eventually they will be exhausted and the current cost of automotive fuel is evidence of them becoming diminished. The carbon dioxide emissions created through the energy conversion process are causing an increase in the overall atmospheric concentrations, which through global warming may have serious consequences for humanity.Natural sources of energy production can be derived from the Sun through the use of solar and wind generation methods. Converting these sources to electricity requires the technology of power electronics, the central area of research for this dissertation. Solar energy can most easily be harnessed through the photo-electric effect which creates DC electricity. However, the majority of electric loads and transmission require AC electricity. The inverter is the electronic device required for this power conversion. Wind turbines usually create variable voltage and frequency AC that is rectified to DC and then converted to grid type AC through an inverter.Voltage source inverters, their topologies and control are investigated within this dissertation. Voltage control methods are adopted for both stand-alone and grid connected techniques where control of active and reactive power is required. Current control techniques in the form of PI and hysteresis are applied to allow novel interfaces between generation sources to be achieved. Accurate control of the power electronics allows an enhancement in the power production from the renewable energy source. The power electronic device of the DC-DC converter, either buck or boost is controlled to allow the renewable resource to operate at its optimum power point. The control aspects and algorithms of these converters are central to this research. The solar algorithms of perturb and observe, and incremental conductance are developed with the latter being more favourable to changing levels of irradiation. The author draws a parallel between rapidly changing solar conditions with normally changing wind states. This analogy with an understanding of the mechanics of PMSG allows a novel wind MPPT algorithm to be developed which is simulated in PSIM. Methods to analyse the usefulness of the algorithm are developed and general conclusions are drawn.Another aim central to the research is the efficient combination of renewable energy sources into a single reliable power system. This forms the multi-function aspect of the research. The interconnection of the sources on the AC or DC sides is investigated for both stand-alone and grid connected topologies. A requirement of the stand-alone system is to provide power when no renewable resources are available causing some form of energy storage to be utilised. Conventional batteries are used, causing the VC-VSI to become bi-directional allowing charging. This is simulated in PSIM and demonstrated as part of the Denmark and Eco Beach projects. Many differing topologies of stand alone, grid connected and edge of grid systems are developed, simulated and some are demonstrated.While investigating the currently used topologies the author invents the novel complimentary hybrid system concept. This idea allows a single inverter to be used to feed energy from either the wind or solar resource. With careful engineering of the PV array and wind turbine characteristics only a small loss of energy is caused, deemed the crossover loss. This original concept is mathematically modelled, simulated and demonstrated with results presented from the Denmark project. The strength of this idea is from the quite complimentary nature of wind and solar resources, for only a small proportion of the year are high solar and strong wind conditions occurring simultaneously.Compared to a solar resource, the wind resource is much more complicated to model. An analysis of readily available wind source data is presented with a statistical analysis of the scaling methods; a novel box and whiskers plot is used to convey this information. New software is presented to allow a more accurate and digital model of a power curve to be recreated, allowing a more precise annual energy generation calculation. For various wind turbines a capacity factor analysis is presented with its disadvantages explained. To overcome these issues the concepts of economic efficiency and conversion efficiency are explained. These prevent some of the typical methods to enhance the standard capacity factor expression. The combination of these three methods allows selection of the most suitable wind turbine for a site.The concept of a mini-grid is an isolated power generation and distribution system, which can have its renewable energy sources, centralised or decentralised. The methods used to coalesce conventional generation with renewable energy technology forms another key piece of this research. A design methodology for the development of a hybrid power system is created with examples used from projects attributed to the author. The harmonising of the renewable energy sources with the conventional generation while providing a stable and robust grid is explained in detail with respect to the generator loading and control. The careful control of the renewable resource output is shown to allow a greater overall penetration of renewable energy into the network while continuing network stability. The concept of frequency shift control is presented, simulated and demonstrated with reference to the Eco Beach project. This project epitomises much of the research that has been presented in this dissertation. It combines centralised and decentralised inverters, with battery storage and the control of diesel generators. An overall controller dictates the optimum times to charge or draw from the battery based upon the local environmental and time of day variables. Finally, the monitoring aspects of this project are representative of a future smart grid where loads may be shed on demand through under frequency or direct control.